Exploring Consumer Experiences of Barriers and Enablers to Accessing Rehabilitation That Meets Their Needs: The Rehabilitation Choices Study, Part 2—Consumer Perspectives - Gillian Mason; Karen Ribbons; Lucy Bailey; Adrian O'Malley; Tracy Ward; Stephen Ward; Michael Pollack; Frederick R. Walker; Michael Nilsson; Nicolette Hodyl (Health Expectations)
ABSTRACT Introduction Improved access to rehabilitation is highlighted as a key pathway to achieving the World Health Organisation's (WHO) goal of ensuring healthy lives and promoting well‐being for all (Sustainable Development Goal 3). This article is the second in a two‐part series outlining the findings from the Rehabilitation Choices study, which aimed to identify how health professionals and consumers in Australia are informed to make decisions about rehabilitation, and their experience with barriers and enablers to accessing that rehabilitation. In this study, we present the perspectives of consumers with different health conditions and a range of experiences with rehabilitation services. Methods This was a qualitative study using focus groups and semi‐structured interviews. People with self‐reported lived experience of rehabilitation and carers were recruited using maximum variation sampling. Thematic analysis of data was conducted using an inductive approach. Results Fifty‐six consumers with diverse lived experiences of rehabilitation (19–80 years, 49 patients, 7 carers) participated in focus groups and interviews to discuss how they sourced information about rehabilitation and their experiences of what made it hard or easy to access rehabilitative care to meet their needs. Four themes were produced from the data: (1) service‐centricity of options limits access, (2) access is the patient's responsibility, (3) enabling decision‐making about rehabilitation with appropriate information and (4) provision of a psychologically safe environment. Conclusions Any planned (re)design of services to improve consumer access to rehabilitation should consider the themes identified in this study. This will ensure that consumers are provided with rehabilitation options that suit their holistic and unique needs beyond consideration of their medical diagnoses, and are actively supported to navigate this access, provided with information to help them make informed choices and provided a psychologically safe environment to engage effectively with rehabilitation. Patient or Public Contribution Three consumer research partners with lived experience of rehabilitation as patients or carers were core team members. They were involved in the design and implementation of the recruitment and communications strategies, design of the interview approach and discussion guide, contributed to the interpretation and contextualisation of findings and writing of this manuscript and are included as co‐authors (A. O., T. W. and S. W.).